White Light —White Heat: The use of Fire as a Light and Heat Source in an Atrium House in Roman Pompeii - Boman, Henrik (Current Swedish Archaeology, 2005)
This article concerns the distribution of fire as light and heat source within the insula investigated by the ongoing Swedish Pompeii Project. Here the author suggests that fire installations as kitchens, ovens and baths were clustered in specific areas within this insula, and the installations were not efficiently used to heat the dwelling areas of the house. It is also proposed that the surfaces of the interior walls and floors of the Roman atrium house were polished in purpose to reflect and distribute light and, which is emphasised in the article, to soften the transition between brightly lit areas and areas in dark shadow. This contrast had to be eliminated for the human eye to adopt to the light conditions in the room and by that, to make the light as efficient as possible.